QUALITY ASSESSMENT OF SMOKE-DRIED CATFISH STORED IN DIFFERENT PACKAGING MATERIALS - Oshoke, Justina O.; Sadiq, Hauwa O.; Yahaya, Zainab (FUDMA JOURNAL OF SCIENCES, 2025)
The perishable nature of fish necessitates its proper handling and preservation to increase its shelf-life and retain its desirable quality and nutritional value. This work aimed to evaluate the effects different packaging materials on the proximate and microbial analysis of smoked dried African Catfish (Clarias gariepinus). Freshly harvested fish was purchased from Zobe dam in Dutsin-Ma Local Government Area of Katsina State, Nigeria. A total of thirty (30) sample of C. gariepinus weighing 7.2kg were bought and divided into Ten (10) fish per treatment. The fish were smoked dried to a constant weight, packaged in three different materials and stored in the laboratory for six (6) weeks. Samples were then taken out from storage for further analysis biweek and finally concluded at six weeks. The analysis done was proximate composition, bacterial and fungal count. The result of the proximate assessment at the 6th week shows that the range for moisture was 10.1%-15.8%, protein, 51.1%-58.4%, 1.53%-2.40%, ash, 1.53%-2.40% and lipid, 19.6%-21.4%. Total viable count increased in week 6 with paper bag having the highest number of 9.3x105 cfu/g of bacteria and 8.4x105 of fungal. The least count for bacterial and fungal was recorded in transparent zip-lock bag and zip-lock aluminum foil bag. The results showed that the most suitable packaging material were both transparent zip-lock bag and zip-lock aluminum foil bag. This is because the preserved the quality of the fish hence the proximate composition of the fish was better than the fish kept in paper bag.
Keywords: Catfish; Packaging; Transparent zip-lock bag; Zip-lock aluminum foil bag; Paper bag